Adverse muscle composition predicts all‐cause mortality in the UK Biobank imaging study. Issue 6 (29th October 2021) - Linge, Jennifer; Petersson, Mikael; Forsgren, Mikael F.; Sanyal, Arun J.; Dahlqvist Leinhard, Olof
Abstract: Background: Adverse muscle composition (MC) as measured by magnetic resonance imaging has previously been linked to poor function, comorbidity, and increased hospitalization. The aim of this study was to investigate if adverse MC predicts all‐cause mortality using data from UK Biobank. Methods: There were 40 178 participants scanned using a 6 min magnetic resonance imaging protocol. Images were analysed for thigh fat‐tissue free muscle volume and muscle fat infiltration (MFI) using AMRA® Researcher (AMRA Medical, Linköping, Sweden). For each participant, a sex, weight, and height invariant muscle volume z‐score was calculated. Participants were partitioned into four MC groups: (i) normal MC, (ii) only low muscle volume [<25th percentile for muscle volume z‐score (population wide)], (iii) only high MFI [>75th percentile (population wide, sex‐specific)], and (iv) adverse MC (low muscle volume z‐score and high MFI). Association of MC groups with mortality was investigated using Cox proportional‐hazard modelling with normal MC as referent (unadjusted and adjusted for low hand grip strength, sex, age, body mass index, previous diagnosis of disease (cancer, type 2 diabetes and coronary heart disease), lifestyle, and socioeconomic factors (smoking, alcohol consumption, physical activity, and Townsend deprivation index). Results: Muscle composition measurements were complete for 39 804 participants [52% female, mean (SD) age 64.2 (7.6) years and body mass index 26.4 (4.4) kg/m 2 ]. Three hundred twenty‐eight deaths were recorded during a follow‐up period of 2.9 (1.4) years after imaging. At imaging, adverse MC was detected in 10.5% of participants. The risk of death from any cause in adverse MC compared with normal MC was 3.71 (95% confidence interval 2.81–4.91, P < 0.001). Only low muscle volume and only high MFI were independently associated with all‐cause mortality [1.58 (1.13–2.21), P = 0.007, and 2.02 (1.51–2.71), P < 0.001, respectively]. Adjustment of low hand grip strength [1.77 (1.28–2.44), P < 0.001] did not attenuate the associations with any of the MC groups. In the fully adjusted model, adverse MC and only high MFI remained significant ( P < 0.001 and P = 0.020) while the association with only low muscle volume was attenuated to non‐significance ( P = 0.560). The predictive performance of adverse MC [1.96 (1.42–2.71), P < 0.001] was comparable with that of previous cancer diagnosis [1.93 (1.47–2.53), P < 0.001] and smoking [1.71 (1.02–2.84), P = 0.040]. Low hand grip strength was borderline non‐significant [1.34 (0.96–1.88), P = 0.090]. Conclusions: Adverse MC was a strong and independent predictor of all‐cause mortality. Sarcopenia guidelines can be strengthened by including cut‐offs for myosteatosis enabling detection of adverse MC .